Continuous dynamic monitoring of bridges: different perspectives of application - Álvaro Cunha (2013)
This paper makes a brief characterisation of some aspects related with the extensive research activity of the Laboratory of Vibrations and Structural Monitoring (ViBest) of the Faculty of Engineering of the University of Porto (FEUP) in the field of Continuous Dynamic Monitoring of Bridges and Special Structures, selecting four examples where large high quality databases have been created since 2007, namely Infante D. Henrique bridge, Pedro e Ines footbride, FEUP Campus stress-ribbon footbridge and Trezoi railway bridge.